Efficacy and safety of flexibly dosed brexpiprazole for the adjunctive treatment of major depressive disorder: a randomized, active-referenced, placebo-controlled study. (3rd April 2018) - Hobart, Mary; Skuban, Aleksandar; Zhang, Peter; Josiassen, Mette Krog; Hefting, Nanco; Augustine, Carole; Brewer, Claudette; Sanchez, Raymond; McQuade, Robert D.
Abstract: Objective: To assess the efficacy, safety, and tolerability of brexpiprazole as adjunctive treatment in adults with major depressive disorder (MDD) and an inadequate response to prior antidepressant treatment (ADT). Methods: Patients with a current major depressive episode after prior treatment with 1−3 ADTs entered an 8- or 10-week prospective treatment phase in which they received double-blind placebo adjunct to open-label ADT. Inadequate responders were randomized (2:2:1) to brexpiprazole 2−3 mg/day, placebo, or quetiapine extended-release (XR) 150−300 mg/day, adjunct to the same ADT, for 6 weeks. The primary efficacy endpoint was the change from baseline (randomization) to week 6 in Montgomery−Åsberg Depression Rating Scale (MADRS) total score. The key secondary efficacy endpoint was the change in Sheehan Disability Scale (SDS) mean score. Results: Adjunctive brexpiprazole showed a greater improvement in MADRS total score than adjunctive placebo (least squares mean difference [95% confidence interval] = −1.48 [−2.56, −0.39]; p = .0078), whereas adjunctive quetiapine XR did not separate from placebo (−0.30 [−1.63, 1.04]; p = .66). Adjunctive brexpiprazole failed to separate from placebo on the SDS mean score (−0.23 [−0.52, 0.07]; p = .13), but did improve functioning on two of the three SDS items (family life and social life). The most frequent treatment-emergent adverse events in patients receiving brexpiprazole were akathisia (6.1%), somnolence (5.6%), and headache (5.6%). Conclusions: Adjunctive brexpiprazole 2−3 mg/day improved symptoms of depression compared with adjunctive placebo in patients with MDD and an inadequate response to ADTs, and was well tolerated with no unexpected side effects.